Lexicogrammatical Features in Introduction Sections of Research Articles Published in the International Quality Journals - Faizatul Istiqomah; Binti Maunah (ELITE Association Indonesia, 2023)
To participate in global academia, expert and novice researchers are strongly encouraged to publish their academic papers in international journals. Hence, a remarkable ability to produce quality academic writing, which includes knowledge of linguistics features, is a necessity. This paper aimed at exploring lexicogrammatical properties focusing on grammatical intricacy and lexical density deployed within the introduction sections of research articles (RA) published in four international journals in the Asian region. The corpus of 40 introduction sections of RAs was analyzed based on the Systemic Functional Linguistics framework. The results of this study highlighted the structural complexity indicated by the use of paratactic and hypotactic clauses which led to lexically dense academic writing. Some pedagogical implications and recommendations related to the findings were discussed further in this article's final part. Keywords: Grammatical intricacy; introduction sections; lexical density; research articles